Enhanced magnetic properties and improved corrosion performance of nanocrystalline Pr-Nd-Y-Fe-B spark plasma sintered magnets. (1st December 2020) - Jiang, Qingzheng; Song, Jie; Huang, Qingfang; Rehman, Sajjad Ur; He, Lunke; Zeng, Qingwen; Zhong, Zhenchen
Abstract: Recently it is a hot topic to make full use of high abundant Y element in Nd2 Fe14 B-type permanent magnets. In contrast to Pr and Nd elements, Y shows different metallurgical behaviors during preparation process. In this paper, we have explored the magnetic properties, microstructures and corrosion performance of Pr-Nd-Y-Fe-B magnets fabricated by spark plasma sintering (SPS) technique from the ribbons of nanocrystalline and amorphous precursors, respectively. The coercivity and maximum energy product were improved for the magnets prepared from amorphous precursor materials (denoted as SPS-A hereafter) compared with the magnets prepared from crystalline precursor materials (denoted as SPS-C hereafter). Magnetic properties of J r = 0.79 T, H ci = 864 kA/m, and (BH)max = 102 kJ/m 3 were obtained for SPS-A magnets. In contrast with SPS-C magnets, the magnetic properties of SPS-A magnets are not so sensitive to the preparation conditions, which is quite beneficial to the homogeneity of microstructure and enhancement of coercivity for large-scale production of the designated magnets. Aggregated (Pr, Nd, Y)-rich phase was found out in SPS-C magnets. Pr and Nd elements are rich at grain boundary while Y is distributed uniformly at main phase and grain boundary phase. The strip grains and equiaxed grains exist in SPS-C and SPS-A magnets, respectively. The enhanced magnetic properties for SPS-A magnets are accredited to the uniform distribution of rare-earth-rich phase and low demagnetization factor. It is revealed by electrochemical test and dipping test that the corrosion potential is more positive and the corrosion rate is slower for the SPS-A magnets in 3.5 wt.% NaCl solution. The work is also expected to shed light on developing the nanocrystalline Pr-Nd-Y-Fe-B SPSed high-performance magnets in industry.